2006
DOI: 10.1182/blood-2006-01-011072
|View full text |Cite
|
Sign up to set email alerts
|

Asthma is associated with acute chest syndrome and pain in children with sickle cell anemia

Abstract: Pain and acute chest syndrome (ACS) episodes are 2 of the most common causes of hospitalization in children with sickle cell anemia (SCA). However, very few potentially modifiable risk factors for either condition have been identified. In this prospective infant cohort study, we tested the hypothesis that asthma is associated with an increased incidence rate of pain and ACS episodes. An infant cohort was composed of 291 African American children with hemoglobin SS enrolled in the Cooperative Study for Sickle C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
222
2
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(240 citation statements)
references
References 28 publications
14
222
2
2
Order By: Relevance
“…Readmission was less frequent in patients with many episodes of ACS and after transfusion. Asthma was associated with recurrent ACS in Jamaican children [18] and an increased rate of admission for ACS and painful crisis, but not prolonged hospitalization, in the infant cohort of the CSSCD [19]. However, most patients in our study who were treated with dexamethasone did not have a history of asthma or wheezing at the time of treatment, as recognized asthma exacerbations typically were treated with other corticosteroids (prednisone or prednisolone).…”
Section: Discussionmentioning
confidence: 65%
“…Readmission was less frequent in patients with many episodes of ACS and after transfusion. Asthma was associated with recurrent ACS in Jamaican children [18] and an increased rate of admission for ACS and painful crisis, but not prolonged hospitalization, in the infant cohort of the CSSCD [19]. However, most patients in our study who were treated with dexamethasone did not have a history of asthma or wheezing at the time of treatment, as recognized asthma exacerbations typically were treated with other corticosteroids (prednisone or prednisolone).…”
Section: Discussionmentioning
confidence: 65%
“…Knight-Madden et al 4 reported that children with sickle cell disease were more than twice as likely to have asthma or bronchial hyperreactivity, and that asthma was more common in children who had suffered recurrent episodes of ACS. Boyd et al 5 reported from the Cooperative Study for Sickle Cell Disease that the frequency of ACS events was twice as high in patients with a diagnosis of asthma. Duckworth et al 6 reported a relationship between physician-diagnosed asthma and ACS.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] The presence of asthma in SCD has been associated with increased risk of developing ACS. In addition, the first ACS event tends to occur at a younger age when compared to patients who do not have asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Boyd et al [38] and Lewis et al [39] found lower haemoglobin and elevated white blood cells concentrations in asthmatics when compared with non-asthmatics. The disparity with regards to serum protein and serum calcium levels in blood among the two groups may be due to fewer intakes of calcium and protein rich food items in their diet.…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%